Managing in a global economy : - Marthinsen, John E. (Thomson South-Western, 2008)
The book was written for MBAs who were not necessarily economics majors, making it appealing to students with a variety of undergraduate backgrounds. Marthinsen keeps readers visually engaged with strategic use of figures, tables, charts, and illustrative exhibits. MANAGING IN A GLOBAL ECONOMY offers a strategic focus, emphasizes the interaction among markets, and equips MBAs with a macroeconomic perspective that will last (and be used) for years.